Effectiveness of Virtual Anatomy System (VAS) Media to Improve Students’ Analysis Ability Towards Reproduction System Materials - Dyah Setyaningrum Winarni (Indonesian Journal of Science and Education (IJOSE), 2020)
This research aims to identify effectiveness of virtual anatomy system (VAS) media with inquiry approach in improving students’ analysis ability towards reproduction system materials. VAS is a learning media which was developed with a special design resembling a laboratory, equipped with tools and materials, as well as operational procedures in a pratice. The method employed in this research was a quasi - experiment with one group pretest posttest design. The sample consisted of 12 students. The Ngain (0,67) produced belonged to the medium category. The result confirmed that the students’ responses using VAS with inquiry approach improved in reproduction system materials. Hence, it can be concluded that VAS media with inquiry approach was highly effective in improving Ivet University students’ analysis ability in understanding the reproduction system optimally.Keywords: Virtual Anatomy System, Inquiry, Analysis Abilty, Reproduction System